Low-temperature cured perovskite photovoltaic cell and preparation method
Patent Information
- Application Number
- CN202611457654.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-18
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]上述技术为钙钛矿界面钝化和稳定性提升提供了不同思路,但对于同时兼顾未配位金属缺陷钝化、卤素离子迁移抑制、低温成膜和界面阻隔稳定性的功能层,仍有进一步优化空间
本发明将阳离子卤素固定基团、Lewis碱配位基团、氟硅阻隔链段以及低温交联基团集成于同一离子-配位-氟硅双固化化合物中,使低温固化功能层同时具备界面钝化、离子迁移抑制、阻隔保护和低温交联成网作用;低温固化功能层设置于钙钛矿吸光层与第二电荷传输层之间,能够直接作用于影响载流子抽取和界面稳定性的关键界面。
Smart Images

Figure CN123021887A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of photovoltaic cell materials and device manufacturing technology, specifically to a low-temperature curing perovskite photovoltaic cell and its preparation method. Background Technology
[0002] Perovskite photovoltaic cells possess advantages such as solution processing, tunable bandgap, and high absorption coefficient. In typical device structures, the interfacial state between the perovskite light-absorbing layer and the charge transport layer affects carrier extraction, interfacial recombination, ion migration, and device stability. Therefore, setting passivation layers, modification layers, or protective layers on the surface of the perovskite light-absorbing layer is a common improvement direction in this field.
[0003] Existing technologies include methods for treating lead halide perovskite thin films using polymerizable acrylic-based small molecules. These methods coat the surface of a crystalline perovskite film with acrylic-based small molecules and then cure them under room temperature light to form a modification layer, thereby improving the film's hydrophobicity and surface defect state. This approach primarily relies on an acrylic-based free radical photocuring system to form passivation or protective structures.
[0004] In existing technologies, there are also schemes that use self-crosslinking siloxane molecules to modify the surface of perovskite thin films. These molecules may contain electron-rich groups such as imidazole, amidine, carboxyl, phosphate, guanidine, and thiourea groups to interact with uncoordinated metal ions on the perovskite surface; at the same time, the siloxane groups can undergo hydrolysis and condensation to form a modified layer with certain hydrophobicity.
[0005] In the prior art, there are also perovskite solar cells based on DCL cross-linked interface passivation layers. This type of approach can form a cross-linked interface passivation layer on the perovskite light-absorbing layer, which interacts with perovskite surface defects through anchoring groups and forms a cross-linked network under certain annealing conditions.
[0006] The above technologies offer different approaches to perovskite interface passivation and stability enhancement, but there is still room for further optimization for functional layers that simultaneously achieve passivation of uncoordinated metal defects, suppression of halide ion migration, low-temperature film formation, and interfacial barrier stability. Summary of the Invention
[0007] The purpose of this invention is to provide a low-temperature curing perovskite photovoltaic cell and its preparation method, which enables the formation of a functional layer between the perovskite light-absorbing layer and the charge transport layer without high-temperature treatment. This layer combines interface passivation, halide ion fixation, barrier protection, and low-temperature cross-linking network formation.
[0008] To achieve the above objectives, the present invention adopts the following technical solution: The present invention provides a low-temperature curing perovskite photovoltaic cell, comprising a transparent conductive substrate, a first charge transport layer, a perovskite light-absorbing layer, a second charge transport layer and a back electrode, wherein a low-temperature curing functional layer with a thickness of 5nm~120nm is disposed between the perovskite light-absorbing layer and the second charge transport layer. The low-temperature curing functional layer is formed by in-situ curing of the low-temperature curing composition. Based on a total mass of 100 parts of ion-coordination-fluorosilicone dual-curing compound, cationic ring-opening curable matrix, latent acid initiator and silane condensation catalyst, the low-temperature curing composition includes 15-70 parts of ion-coordination-fluorosilicone dual-curing compound, 25-85 parts of cationic ring-opening curable matrix, 0.1-4 parts of latent acid initiator and 0.01-1 parts of silane condensation catalyst. The ion-coordination-fluorosilicone dual-curing compound is a siloxane oligomer obtained by pre-hydrolysis condensation of fluorinated alkyl alkoxysilanes, Lewis base silanes, cationic silanes, and epoxy silanes and / or oxetane silanes; the siloxane oligomer simultaneously contains fluorosilicone barrier segments, Lewis base coordination groups, cationic halogen fixing groups, and epoxy and / or oxetane groups, and contains alkoxysilanes that can be further hydrolyzed and condensed.
[0009] Preferably, the molar ratio of the fluorinated alkyl alkoxysilane, Lewis base silane, cationic silane to epoxy silane and / or oxetane silane is 1~5:0.5~2:0.5~2:1~4.
[0010] Preferably, the fluorinated alkyl alkoxysilane is selected from one or two of trimethoxy(3,3,3-trifluoropropyl)silane and triethoxy(1H,1H,2H,2H-perfluorooctyl)silane; the Lewis base silane is selected from one or two of N,N'-bis(3-triethoxysilylpropyl)thiourea and 1-[3-(trimethoxysilyl)propyl]urea; the cationic silane is selected from one or two of N-[3-(trimethoxysilyl)propyl]-N,N,N-trimethylammonium chloride and 1-methyl-3-[3-(trimethoxysilyl)propyl]imidazolium chloride; and the epoxy silane and / or oxetane silane is selected from one or two of 3-glycidoxypropyltrimethoxysilane and 3-ethyl-3-[[3-(triethoxysilyl)propoxy]methyl]oxetane.
[0011] Preferably, the thickness of the low-temperature curing functional layer is 8nm~80nm; and the amount of the ion-coordination-fluorosilicone dual-curing compound is 20~55 parts.
[0012] Preferably, the cationic ring-opening curable matrix is selected from one or more of 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane, 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexane carboxylate, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and 3-ethyl-3-[[3-(triethoxysilyl)propoxy]methyl]oxetane.
[0013] Preferably, the low-temperature curing composition further includes surface-modified nano-barrier filler; relative to 100 parts by total mass of the ion-coordination-fluorosilicone dual-curing compound, the cationic ring-opening curable matrix, the latent acid initiator and the silane condensation catalyst, the surface-modified nano-barrier filler is 0.1 to 5 parts. The surface-modified nanobarrier filler is selected from one or more of the following: nano-SiO2 treated with triethoxy(1H,1H,2H,2H-perfluorooctyl)silane, nano-Al2O3 treated with 3-glycidoxypropyltrimethoxysilane, and sheet-like BN treated with triethoxy(1H,1H,2H,2H-perfluorooctyl)silane. The average particle size or sheet size of the surface-modified nanobarrier filler is 10 nm to 300 nm.
[0014] Preferably, the perovskite light-absorbing layer is made of ABX3 type perovskite material, wherein the A-site cation includes one or more of methylamine ions, formamidinium ions, cesium ions, and rubidium ions; the B-site metal ion includes lead ions and / or tin ions; and the X-site halide ion includes one or more of iodide ions, bromide ions, and chloride ions. The first charge transport layer and the second charge transport layer are independently selected from electron transport layers or hole transport layers, wherein the electron transport layer includes one or more of SnO2, TiO2, ZnO, C60, and PCBM, and the hole transport layer includes NiO. x One or more of PTAA, Spiro-OMeTAD, PEDOT:PSS, and CuSCN.
[0015] This invention also provides a method for preparing the above-mentioned low-temperature curing perovskite photovoltaic cell, comprising the following steps: S1. Provide a transparent conductive substrate and form a first charge transport layer on the transparent conductive substrate; S2. A perovskite light-absorbing layer is formed on the first charge transport layer; S3. Coat the side of the perovskite light-absorbing layer away from the first charge transport layer with a low-temperature curing composition; S4. The perovskite light-absorbing layer coated with the low-temperature curing composition is subjected to light irradiation treatment of 365 nm to 405 nm and heat treatment at 40°C to 100°C, so that the low-temperature curing composition forms a functional layer with a thickness of 5 nm to 120 nm in situ on the surface of the perovskite light-absorbing layer. S5. A second charge transport layer and a back electrode are formed on the low-temperature curing functional layer to obtain the low-temperature curing perovskite photovoltaic cell.
[0016] Preferably, before step S3, the method further includes a step of preparing the low-temperature curing composition: dissolving the cationic ring-opening curable matrix in a solvent, adding the ion-coordination-fluorosilicone dual-curing compound and stirring for 10 min to 120 min, then adding the latent acid initiator and the silane condensation catalyst, stirring in the dark for 5 min to 60 min, and then filtering through a 0.1 μm to 0.45 μm filter membrane; the solvent is selected from one or more of isopropanol, ethyl acetate, toluene, chlorobenzene, anisole, butyl acetate, methyl tert-butyl ether and fluoroether solvents.
[0017] Preferably, in step S3, the coating method is spin coating, blade coating, slot coating, spray coating, or inkjet printing; when spin coating is used, the rotation speed is 1500rpm~5000rpm and the time is 10s~60s; in step S4, the 365nm~405nm light irradiation time is 10s~300s, and the 40℃~100℃ heat treatment time is 1min~20min; after step S4, a post-processing step of standing at 20℃~60℃ for 30s~10min is also included.
[0018] The mechanism of action of this invention lies in the fact that the Lewis base coordination group can interact with uncoordinated lead ions and / or tin ions on the surface of the perovskite light-absorbing layer, thereby helping to reduce interface defects and non-radiative recombination; the cationic halogen fixing group can form electrostatic interactions or ionic associations with iodide ions, bromide ions or chloride ions in the perovskite, thereby helping to inhibit the migration and accumulation of halogen ions at the interface; the fluorosilicone barrier segment has a low surface energy, and the alkoxysilane contained therein can undergo hydrolysis and condensation reactions, which is beneficial to forming an interface microenvironment with good barrier properties; the epoxy group and / or oxobutane can undergo cationic ring-opening curing under the action of a latent acid initiator, and together with the cationic ring-opening curable matrix, form a cross-linked network. The above-mentioned cationic ring-opening curing and alkoxysilane condensation curing work together to form a dual-curing network.
[0019] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: This invention integrates cationic halogen fixing groups, Lewis base coordination groups, fluorosilicone barrier segments, and low-temperature crosslinking groups into the same ion-coordination-fluorosilicone dual-curing compound, enabling the low-temperature curing functional layer to simultaneously possess interface passivation, ion migration inhibition, barrier protection, and low-temperature crosslinking network functions. The low-temperature curing functional layer is disposed between the perovskite light-absorbing layer and the second charge transport layer, and can directly act on the key interfaces that affect carrier extraction and interface stability.
[0020] The low-temperature curing composition of the present invention, through the combination of a latent acid initiator and a silane condensation catalyst, can form a stable functional layer at a temperature not exceeding 110°C, which is beneficial to improving the process compatibility with perovskite light-absorbing layers. The formulation ratio, layer thickness and curing conditions of the present invention can be adjusted by coating concentration, coating method, light irradiation time and heat treatment time, which is convenient for subsequent expansion to different device structures and different coating processes. Attached Figure Description
[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1 This is a schematic diagram of the layered structure of the low-temperature curing perovskite photovoltaic cell of the present invention.
[0023] Figure 2 This is a schematic diagram illustrating the working mechanism of each functional structural unit in the low-temperature curing functional layer of the present invention.
[0024] Figure 3 This is a schematic flowchart of the low-temperature curing perovskite photovoltaic cell preparation method of the present invention. Detailed Implementation
[0025] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0026] See Figure 1As shown, the low-temperature curing perovskite photovoltaic cell of the present invention includes a transparent conductive substrate, a first charge transport layer, a perovskite light-absorbing layer, a low-temperature curing functional layer, a second charge transport layer, and a back electrode. The low-temperature curing functional layer is located between the perovskite light-absorbing layer and the second charge transport layer, thus enabling it to simultaneously contact the perovskite surface and the subsequently formed charge transport layer.
[0027] Figure 2 The ion-coordination-fluorosilicone dual-curing compound shown includes a Lewis base coordinating group, a cationic halogen fixing group, a fluorosilicone barrier segment, and epoxy and / or oxetane groups. The Lewis base coordinating group is used to interact with uncoordinated metal ions, the cationic halogen fixing group is used to interact with halide ions, the fluorosilicone barrier segment is used to improve the hydrophobic barrier properties of the interface, and the epoxy and / or oxetane groups are used to form a low-temperature ring-opening curing network.
[0028] Figure 3 The fabrication method shown includes forming a first charge transport layer, forming a perovskite light-absorbing layer, coating a low-temperature curing composition, low-temperature in-situ curing, forming a second charge transport layer, and forming a back electrode. The low-temperature curing functional layer is formed in-situ on the perovskite light-absorbing layer, avoiding interface contamination or adhesion defects that may result from transferring the film layer separately.
[0029] The specific raw materials for preparing the ion-coordination-fluorosilicone dual-curing compound include: trimethoxy(3,3,3-trifluoropropyl)silane, CAS No. 429-60-7; triethoxy(1H,1H,2H,2H-perfluorooctyl)silane, CAS No. 51851-37-7; N,N'-bis(3-triethoxysilylpropyl)thiourea, CAS No. 69952-89-2; 1-[3-(trimethoxysilyl)propyl]urea, CAS No. 23843-64-3; N -[3-(trimethoxysilyl)propyl]-N,N,N-trimethylammonium chloride, CAS No. 35141-36-7; 1-methyl-3-[3-(trimethoxysilyl)propyl]imidazolium chloride, CAS No. 856925-70-7; 3-glycidoxypropyltrimethoxysilane, CAS No. 2530-83-8; 3-ethyl-3-[[3-(triethoxysilyl)propoxy]methyl]oxetane, CAS No. 220520-33-2.
[0030] The raw material for anion exchange is lithium bis(trifluoromethanesulfonyl)imide, CAS No. 90076-65-6. Through anion exchange, the chloride ions in some quaternary ammonium salt or imidazolium salt structures are replaced with bis(trifluoromethanesulfonyl)imide ions to reduce the potential impact of free halide ions on the interface.
[0031] The cationic ring-opening curable matrix uses 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane, CAS No. 126-80-7; 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexane carboxylate, CAS No. 2386-87-0; 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, CAS No. 3388-04-3; and 3-ethyl-3-[[3-(triethoxysilyl)propoxy]methyl]oxetane, CAS No. 220520-33-2.
[0032] The latent acid initiator is bis[4-(diphenylsulfonium)phenyl]sulfide bis(hexafluorophosphate), CAS No. 74227-35-3; alternatively, commercially available sulfonium salt photoacid initiators containing diphenyl(4-phenylthio)phenylsulfonium hexafluorophosphate may be used. The silane condensation catalyst can be tetrabutyl titanate, CAS No. 5593-70-4.
[0033] In this embodiment of the invention, the ion-coordination-fluorosilicone dual-curing compound can be prepared as follows: trimethoxy(3,3,3-trifluoropropyl)silane, N,N'-bis(3-triethoxysilylpropyl)thiourea, N-[3-(trimethoxysilyl)propyl]-N,N,N-trimethylammonium chloride and 3-ethyl-3-[[3-(triethoxysilyl)propoxy]methyl]oxetane are weighed in a molar ratio of 3.0:1.0:1.0:1.5 and added to anhydrous ethanol; deionized water is added at a molar ratio of water to alkoxysilane of 0.25:1, and the system is adjusted to weak acidity with acetic acid. The mixture is stirred at 25°C for 2 h and then stirred at 50°C for 4 h to obtain a chloride-containing precondensation oligomer. Subsequently, lithium bis(trifluoromethanesulfonyl)imide was added at a molar ratio of 1:1.1 to the cationic group, and anion exchange was performed in acetonitrile to remove the by-product salt and remove the solvent, yielding ion-coordination-fluorosilicon dual-cured compound one.
[0034] Ion-coordination-fluorosilicone dual-cured compound II can be prepared as follows: Triethoxy(1H,1H,2H,2H-perfluorooctyl)silane, 1-[3-(trimethoxysilyl)propyl]urea, 1-methyl-3-[3-(trimethoxysilyl)propyl]imidazolium chloride and 3-glycidoxypropyltrimethoxysilane are weighed in a molar ratio of 1.2:1.0:1.0:2.0 and treated with the same pre-hydrolysis condensation and anion exchange method as compound I to obtain ion-coordination-fluorosilicone dual-cured compound II.
[0035] Ion-coordination-fluorosilicone dual-curing compound III can be prepared as follows: trimethoxy(3,3,3-trifluoropropyl)silane, 1-[3-(trimethoxysilyl)propyl]urea, N-[3-(trimethoxysilyl)propyl]-N,N,N-trimethylammonium chloride and 3-glycidoxypropyltrimethoxysilane are weighed in a molar ratio of 2.0:0.8:1.2:1.0 and treated with the same pre-hydrolysis condensation and anion exchange method as compound I to obtain ion-coordination-fluorosilicone dual-curing compound III.
[0036] The basic device structure used in this embodiment of the invention is an ITO glass substrate / SnO2 electron transport layer / FA-MA-Cs lead halide perovskite light-absorbing layer / low-temperature curing functional layer / Spiro-OMeTAD hole transport layer / Au back electrode. This basic device structure is only used to illustrate the embodiments of the invention and does not exclude other nip or pin structures. Example 1:
[0037] The method for preparing low-temperature curing perovskite photovoltaic cells in this embodiment includes the following steps: S1. Provide ITO glass as a transparent conductive substrate; ultrasonically clean the ITO glass sequentially with cleaning agent, deionized water, acetone and isopropanol, dry it with nitrogen and then treat it with ultraviolet ozone for 15 min; spin-coat the treated ITO glass with SnO2 colloidal dispersion at 3000 rpm for 30 s, and then anneal it at 150°C for 30 min to form SnO2 electron transport layer as the first charge transport layer; S2. Spin-coat a perovskite precursor solution containing FAI, MABr, CsI, PbI2 and PbBr2 onto the SnO2 electron transport layer. Chlorobenzene is added dropwise as an antisolvent during the spin-coating process. Then, anneal at 100°C for 10 min to form a FA-MA-Cs lead halide perovskite light-absorbing layer. S3. Based on a total mass of 100 parts of ion-coordination-fluorosilicone dual-cured compound I, 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane, bis[4-(diphenylsulfonium)phenyl]sulfide bishexafluorophosphate, and tetrabutyl titanate, weigh out 40.0 parts of ion-coordination-fluorosilicone dual-cured compound I, 58.6 parts of 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane, 1.2 parts of bis[4-(diphenylsulfonium)phenyl]sulfide bishexafluorophosphate, and 0.2 parts of tetrabutyl titanate; First, 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane was dissolved in a mixed solvent of ethyl acetate and chlorobenzene. Then, an ion-coordination-fluorosilicone dual-curing compound was added and stirred for 60 min. Subsequently, bis[4-(diphenylsulfonium)phenyl]sulfide bis(hexafluorophosphate) and tetrabutyl titanate were added, and the mixture was stirred in the dark for 30 min. After filtration through a 0.22 μm filter membrane, a low-temperature curing composition was obtained. The low-temperature curing composition was spin-coated onto the side of the perovskite light-absorbing layer away from the SnO2 electron transport layer under spin-coating conditions of 4000 rpm for 30 s. S4. Expose the spin-coated sample to 405nm light for 90s and heat-treat it at 80℃ for 10min to cure the low-temperature curing composition in situ, forming a low-temperature curing functional layer with a target thickness of 30nm~50nm; let the sample stand at 25℃ for 2min. S5. Spin-coating a Spiro-OMeTAD hole transport layer onto the low-temperature curing functional layer, and then forming an Au back electrode by thermal evaporation to obtain a low-temperature curing perovskite photovoltaic cell. Example 2:
[0038] The method for preparing low-temperature curing perovskite photovoltaic cells in this embodiment includes the following steps: S1. Provide ITO glass as a transparent conductive substrate; ultrasonically clean the ITO glass sequentially with cleaning agent, deionized water, acetone and isopropanol, dry it with nitrogen and then treat it with ultraviolet ozone for 15 min; spin-coat SnO2 colloidal dispersion onto the treated ITO glass at 3000 rpm for 30 s, and then anneal it at 150℃ for 30 min to form a SnO2 electron transport layer. S2. Spin-coat a perovskite precursor solution containing FAI, MABr, CsI, PbI2 and PbBr2 onto the SnO2 electron transport layer. Chlorobenzene is added dropwise as an antisolvent during the spin-coating process. Then, anneal at 100°C for 10 min to form a FA-MA-Cs lead halide perovskite light-absorbing layer. S3. Based on a total mass of 100 parts of ion-coordination-fluorosilicone dual-cured compound II, 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexane carboxylate, bis[4-(diphenylsulfonium)phenyl]sulfide bishexafluorophosphate, and tetrabutyl titanate, weigh 35.0 parts of ion-coordination-fluorosilicone dual-cured compound II, 62.7 parts of 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexane carboxylate, 2.0 parts of bis[4-(diphenylsulfonium)phenyl]sulfide bishexafluorophosphate, and 0.3 parts of tetrabutyl titanate; first, 3,4... -Epoxycyclohexylmethyl-3',4'-epoxycyclohexane carboxylic acid ester was dissolved in a mixed solvent of ethyl acetate and methyl tert-butyl ether, and then ion-coordination-fluorosilicone dual-curing compound II was added and stirred for 60 min. Subsequently, bis[4-(diphenylsulfonium)phenyl]sulfide bis(hexafluorophosphate) and tetrabutyl titanate were added, and the mixture was stirred in the dark for 30 min. After filtration through a 0.22 μm filter membrane, a low-temperature curing composition was obtained. The low-temperature curing composition was spin-coated onto the side of the perovskite light-absorbing layer away from the SnO2 electron transport layer under spin-coating conditions of 3500 rpm for 30 s. S4. Expose the spin-coated sample to 405nm light for 120s and heat-treat it at 70℃ for 15min to cure the low-temperature curing composition in situ, forming a low-temperature curing functional layer with a target thickness of 20nm~60nm; let the sample stand at 25℃ for 2min. S5. Spin-coating a Spiro-OMeTAD hole transport layer onto the low-temperature curing functional layer, and then forming an Au back electrode by thermal evaporation to obtain a low-temperature curing perovskite photovoltaic cell. Implementation: 3:
[0039] The method for preparing low-temperature curing perovskite photovoltaic cells in this embodiment includes the following steps: S1. Provide ITO glass as a transparent conductive substrate; ultrasonically clean the ITO glass sequentially with cleaning agent, deionized water, acetone and isopropanol, dry it with nitrogen and then treat it with ultraviolet ozone for 15 min; spin-coat SnO2 colloidal dispersion onto the treated ITO glass at 3000 rpm for 30 s, and then anneal it at 150℃ for 30 min to form a SnO2 electron transport layer. S2. Spin-coat a perovskite precursor solution containing FAI, MABr, CsI, PbI2 and PbBr2 onto the SnO2 electron transport layer. Chlorobenzene is added dropwise as an antisolvent during the spin-coating process. Then, anneal at 100°C for 10 min to form a FA-MA-Cs lead halide perovskite light-absorbing layer. S3. Based on a total mass of 100 parts of ion-coordination-fluorosilicone dual-cured compound I, 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane, bis[4-(diphenylsulfonium)phenyl]sulfide bis(hexafluorophosphate), and tetrabutyl titanate, weigh out 15.0 parts of ion-coordination-fluorosilicone dual-cured compound I, 84.89 parts of 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane, 0.10 parts of bis[4-(diphenylsulfonium)phenyl]sulfide bis(hexafluorophosphate), and tetrabutyl titanate. 0.01 parts; First, 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane was dissolved in ethyl acetate, then the ion-coordination-fluorosilicone dual-curing compound was added and stirred for 60 min. Subsequently, bis[4-(diphenylsulfonium)phenyl]sulfide bis(hexafluorophosphate) and tetrabutyl titanate were added, and the mixture was stirred in the dark for 30 min. After filtration through a 0.22 μm filter membrane, a low-temperature curing composition was obtained. The low-temperature curing composition was spin-coated onto the side of the perovskite light-absorbing layer away from the SnO2 electron transport layer under spin-coating conditions of 5000 rpm for 60 s. S4. Expose the spin-coated sample to 405nm light for 10s and heat-treat it at 40℃ for 20min to cure the low-temperature curing composition in situ, forming a low-temperature curing functional layer with a target thickness of 5nm~8nm; let the sample stand at 25℃ for 2min. S5. Spin-coating a Spiro-OMeTAD hole transport layer onto the low-temperature curing functional layer, and then forming an Au back electrode by thermal evaporation to obtain a low-temperature curing perovskite photovoltaic cell. Implementation: 4:
[0040] The method for preparing low-temperature curing perovskite photovoltaic cells in this embodiment includes the following steps: S1. Provide ITO glass as a transparent conductive substrate; ultrasonically clean the ITO glass sequentially with cleaning agent, deionized water, acetone and isopropanol, dry it with nitrogen and then treat it with ultraviolet ozone for 15 min; spin-coat SnO2 colloidal dispersion onto the treated ITO glass at 3000 rpm for 30 s, and then anneal it at 150℃ for 30 min to form a SnO2 electron transport layer. S2. Spin-coat a perovskite precursor solution containing FAI, MABr, CsI, PbI2 and PbBr2 onto the SnO2 electron transport layer. Chlorobenzene is added dropwise as an antisolvent during the spin-coating process. Then, anneal at 100°C for 10 min to form a FA-MA-Cs lead halide perovskite light-absorbing layer. S3. Based on a total mass of 100 parts of ion-coordination-fluorosilicone dual-cured compound tris, 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexane carboxylate, bis[4-(diphenylsulfonium)phenyl]sulfide bis(hexafluorophosphate), and tetrabutyl titanate, weigh 70.0 parts of ion-coordination-fluorosilicone dual-cured compound tris, 25.0 parts of 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexane carboxylate, 4.0 parts of bis[4-(diphenylsulfonium)phenyl]sulfide bis(hexafluorophosphate), and 1.0 part of tetrabutyl titanate; first, 3, 4-Epoxycyclohexylmethyl-3',4'-epoxycyclohexane carboxylic acid ester was dissolved in a mixed solvent of butyl acetate and anisole, and then an ion-coordination-fluorosilicone dual-curing compound was added and stirred for 90 min. Subsequently, bis[4-(diphenylsulfonium)phenyl]sulfide bis(hexafluorophosphate) and tetrabutyl titanate were added, and the mixture was stirred in the dark for 30 min. After filtration through a 0.45 μm filter membrane, a low-temperature curing composition was obtained. The low-temperature curing composition was spin-coated onto the side of the perovskite light-absorbing layer away from the SnO2 electron transport layer under spin-coating conditions of 1500 rpm for 20 s. S4. Irradiate the spin-coated sample with 405nm light for 300s and heat-treat it at 100℃ for 20min to cure the low-temperature curing composition in situ, forming a low-temperature curing functional layer with a target thickness of 100nm~120nm; let the sample stand at 40℃ for 2min. S5. Spin-coating a Spiro-OMeTAD hole transport layer onto the low-temperature curing functional layer, and then forming an Au back electrode by thermal evaporation to obtain a low-temperature curing perovskite photovoltaic cell. Example 5:
[0041] The method for preparing low-temperature curing perovskite photovoltaic cells in this embodiment includes the following steps: S1. Provide ITO glass as a transparent conductive substrate; ultrasonically clean the ITO glass sequentially with cleaning agent, deionized water, acetone and isopropanol, dry it with nitrogen and then treat it with ultraviolet ozone for 15 min; spin-coat SnO2 colloidal dispersion onto the treated ITO glass at 3000 rpm for 30 s, and then anneal it at 150℃ for 30 min to form a SnO2 electron transport layer. S2. Spin-coat a perovskite precursor solution containing FAI, MABr, CsI, PbI2 and PbBr2 onto the SnO2 electron transport layer. Chlorobenzene is added dropwise as an antisolvent during the spin-coating process. Then, anneal at 100°C for 10 min to form a FA-MA-Cs lead halide perovskite light-absorbing layer. S3. Based on a total mass of 100 parts of ion-coordination-fluorosilicone dual-cured compound I, 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane, bis[4-(diphenylsulfonium)phenyl]sulfide bis(hexafluorophosphate), and tetrabutyl titanate, weigh out 35.0 parts of ion-coordination-fluorosilicone dual-cured compound I, 63.3 parts of 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane, 1.5 parts of bis[4-(diphenylsulfonium)phenyl]sulfide bis(hexafluorophosphate), and 0.2 parts of tetrabutyl titanate; and add nano-SiO2 surface-treated with triethoxy(1H,1H,2H,2H-perfluorooctyl)silane to a total of 100 parts of the above four solid components. Five parts of the nano-SiO2 were prepared, with an average particle size of 20 nm to 50 nm. The surface-treated nano-SiO2 was first added to ethyl acetate and sonicated for 30 min. Then, 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane and an ion-coordination-fluorosilicone dual-curing compound were added and stirred for 60 min. Subsequently, bis[4-(diphenylsulfonium)phenyl]sulfide bis(hexafluorophosphate) and tetrabutyl titanate were added and stirred in the dark for 30 min. The mixture was then filtered through a 0.45 μm filter membrane to obtain a low-temperature curing composition containing nano-barrier fillers. The low-temperature curing composition was spin-coated onto the side of the perovskite light-absorbing layer away from the SnO2 electron transport layer under spin-coating conditions of 2500 rpm for 30 s. S4. Expose the spin-coated sample to 405nm light for 120s and heat-treat it at 80℃ for 10min to cure the low-temperature curing composition in situ, forming a low-temperature curing functional layer with a target thickness of 60nm~80nm; let the sample stand at 25℃ for 2min. S5. Spin-coating a Spiro-OMeTAD hole transport layer onto the low-temperature curing functional layer, and then forming an Au back electrode by thermal evaporation to obtain a low-temperature curing perovskite photovoltaic cell.
[0042] Comparative Example 1: Comparative Example 1 does not have a low-temperature curing functional layer. After providing ITO glass and forming a SnO2 electron transport layer and a FA-MA-Cs lead halide perovskite light-absorbing layer according to steps S1 and S2 in Example 1, a Spiro-OMeTAD hole transport layer and an Au back electrode are directly formed on the surface of the perovskite light-absorbing layer.
[0043] Comparative Example 2: Comparative Example 2 used a common acrylate free radical photocurable layer. ITO glass was provided, and after forming a SnO2 electron transport layer and a FA-MA-Cs lead halide perovskite light-absorbing layer according to steps S1 and S2 in Example 1, an ethyl acetate solution of pentaerythritol triacrylate and 2-hydroxy-2-methylphenylacetone was spin-coated onto the surface of the perovskite light-absorbing layer. The amount of pentaerythritol triacrylate was 98.8 parts, and the amount of 2-hydroxy-2-methylphenylacetone was 1.2 parts. The spin-coating conditions were 4000 rpm for 30 s, followed by 365 nm illumination for 90 s, forming a common photocurable layer with a thickness of 30 nm to 50 nm. Then, a Spiro-OMeTAD hole transport layer and an Au back electrode were formed.
[0044] Comparative Example 3: Comparative Example 3 employed a single siloxane self-crosslinking modification layer. ITO glass was provided, and after forming a SnO2 electron transport layer and a FA-MA-Cs lead halide perovskite light-absorbing layer according to steps S1 and S2 in Example 1, a siloxane oligomer solution obtained by pre-hydrolysis condensation of trimethoxy(3,3,3-trifluoropropyl)silane, N,N'-bis(3-triethoxysilylpropyl)thiourea, and methyltrimethoxysilane in a molar ratio of 3:1:1 was spin-coated onto the surface of the perovskite light-absorbing layer. The mixture was then heat-treated at 80°C for 10 min to form a modification layer. This modification layer contained no cationic halogen fixing groups, nor any epoxy groups or oxocyclic butyl groups. Subsequently, a Spiro-OMeTAD hole transport layer and an Au back electrode were formed.
[0045] Comparative Example 4: Comparative Example 4 uses a neutral oligomer without cationic halogen-fixed groups to replace the ion-coordination-fluorosilicone dual-curing compound one. This neutral oligomer is obtained by pre-hydrolysis condensation of trimethoxy(3,3,3-trifluoropropyl)silane, N,N'-bis(3-triethoxysilylpropyl)thiourea, 3-ethyl-3-[[3-(triethoxysilyl)propoxy]methyl]oxetane, and methyltrimethoxysilane in a molar ratio of 3.0:1.0:1.5:1.0. Except for replacing the ion-coordination-fluorosilicone dual-curing compound one with this neutral oligomer, the other low-temperature curing composition ratios, coating conditions, curing conditions, preparation of the second charge transport layer, and back electrode are the same as in Example 1.
[0046] Comparative Example 5: Comparative Example 5 uses an oligomer without Lewis base coordinating groups to replace the ion-coordination-fluorosilicone dual-curing compound one. This oligomer is obtained by pre-hydrolysis and condensation of trimethoxy(3,3,3-trifluoropropyl)silane, N-[3-(trimethoxysilyl)propyl]-N,N,N-trimethylammonium chloride, 3-ethyl-3-[[3-(triethoxysilyl)propoxy]methyl]oxetane, and methyltrimethoxysilane in a molar ratio of 3.0:1.0:1.5:1.0, followed by lithium bis(trifluoromethanesulfonyl)imide anion exchange. Except for replacing the ion-coordination-fluorosilicone dual-curing compound one with this oligomer, the preparation steps are the same as in Example 1.
[0047] Comparative Example 6: Comparative Example 6 uses an oligomer without fluorinated silicon barrier segments to replace the ion-coordination-fluorinated silicon dual-curing compound one. This oligomer is obtained by pre-hydrolysis and condensation of methyltrimethoxysilane, N,N'-bis(3-triethoxysilylpropyl)thiourea, N-[3-(trimethoxysilyl)propyl]-N,N,N-trimethylammonium chloride, and 3-ethyl-3-[[3-(triethoxysilyl)propoxy]methyl]oxetane in a molar ratio of 3.0:1.0:1.0:1.5, followed by lithium bis(trifluoromethanesulfonyl)imide anion exchange. Except for replacing the ion-coordination-fluorinated silicon dual-curing compound one with this oligomer without fluorinated silicon barrier segments, the preparation steps are the same as in Example 1.
[0048] Comparative Example 7: Comparative Example 7 uses oligomers that do not contain epoxy groups or oxobutanes and does not contain a cationic ring-opening curable matrix. The oligomer was obtained by pre-hydrolysis and condensation of trimethoxy(3,3,3-trifluoropropyl)silane, N,N'-bis(3-triethoxysilylpropyl)thiourea, N-[3-(trimethoxysilyl)propyl]-N,N,N-trimethylammonium chloride and methyltrimethoxysilane in a molar ratio of 3.0:1.0:1.0:1.0, followed by lithium bis(trifluoromethanesulfonyl)imide anion exchange. ITO glass was provided and, following steps S1 and S2 in Example 1, a SnO2 electron transport layer and a FA-MA-Cs lead halide perovskite light-absorbing layer were formed. Then, the oligomer and an ethyl acetate solution of tetrabutyl titanate were spin-coated, with 99.8 parts of the oligomer and 0.2 parts of tetrabutyl titanate. The spin-coating conditions were 4000 rpm for 30 s. The mixture was then treated under the light and heat treatment conditions of Example 1 to form a Spiro-OMeTAD hole transport layer and an Au back electrode.
[0049] Test example: JV photovoltaic performance testing adopts the measurement caliber of photovoltaic device current-voltage curves as specified in IEC 60904-1:2020. The light source uses AM1.5G simulated sunlight, referencing the ground solar spectral irradiance distribution in IEC 60904-3:2019, with a light intensity of 100 mW / cm².2 The test temperature was 25±2℃, and the effective area was 0.09cm². 2 A metal mask was used to define the effective area. Each group contained 8 samples, and the average value of these 8 samples is recorded in the table. The open-circuit voltage (Voc), current output per unit light-receiving area (Jsc), and fill factor (FF) were also recorded. The reverse scan ranged from 1.2V to 0V, and the forward scan ranged from 0V to 1.2V, with a scan rate of 20mV / s. The hysteresis index was calculated as HI = (reverse scan PCE - forward scan PCE) / reverse scan PCE. The stabilized output test involved tracking near the maximum power point for 300s, and the stabilized PCE was recorded.
[0050] Bias-hold test is used to assist in evaluating interfacial ion migration and bias-induced decay. The test conditions are as follows: first, the initial stabilized PCE is measured, then the device is held in the dark state at 25°C and a bias of 0.9V for 600s, and then the stabilized PCE is measured under the same JV test conditions. The ratio of the stabilized PCE after bias-hold to the initial stabilized PCE is taken as the PCE retention rate after bias-hold.
[0051] Trapped state density was measured using the space charge-limited current method. The single-carrier electronic device structure was ITO / SnO2 / perovskite / test layer / PCBM / Ag. The scanning voltage in the dark state was 0V to 2V, and the trapped state density was calculated based on the trap fill limit voltage.
[0052] The water contact angle test was conducted according to the contact angle test method specified in ISO 19403-2:2024. The test droplet was 2 μL of deionized water, and the test environment was 25±2℃ and relative humidity 45%~55%. Five locations were tested for each sample, and the average value was taken. This test is used to help evaluate the contribution of fluorosilicone barrier segments to the surface hydrophobicity.
[0053] The damp heat stability test was conducted according to the ISOS-D-3 damp heat dark state test standard, with test conditions of 85℃, 85%RH, dark state, and open circuit. All samples were simply encapsulated using the same cover plate and side sealant to reduce the impact of external encapsulation differences on the evaluation of the interface functional layer. The PCE retention rate was recorded after 250h, 500h, and 1000h.
[0054] The specific test results are shown in Tables 1 and 2 below: Table 1. Example 1 1.138 24.5 0.829 23.12 22.52 0.026 22.78 93 Example 2 1.145 24.6 0.830 23.38 22.91 0.020 23.06 94 Example 3 1.122 24.1 0.805 21.78 20.63 0.053 21.05 86 Example 4 1.132 23.7 0.821 22.04 21.01 0.047 21.36 88 Example 5 1.140 24.3 0.821 22.75 22.05 0.031 22.32 94 Comparative Example 1 1.100 24.0 0.772 20.38 18.24 0.105 19.02 74 Comparative Example 2 1.116 24.2 0.790 21.33 19.56 0.083 20.14 80 Comparative Example 3 1.121 24.1 0.797 21.54 20.03 0.070 20.48 83 Comparative Example 4 1.128 24.3 0.800 21.94 19.92 0.092 20.65 78 Comparative Example 5 1.112 24.2 0.802 21.58 20.26 0.061 20.70 84 Comparative Example 6 1.120 24.1 0.783 21.15 19.50 0.078 19.96 81 Comparative Example 7 1.117 24.0 0.791 21.21 19.62 0.075 20.02 82 Table 2. Example 1 2.7 101 90 83 74 Example 2 2.3 98 92 86 78 Example 3 4.1 90 82 70 52 Example 4 3.4 104 86 76 61 Example 5 2.9 106 93 88 81 Comparative Example 1 6.8 61 58 34 15 Comparative Example 2 4.2 88 72 55 34 Comparative Example 3 3.9 96 78 61 41 Comparative Example 4 3.2 100 73 52 30 Comparative Example 5 4.9 102 80 63 43 Comparative Example 6 3.1 74 67 45 24 Comparative Example 7 3.0 95 65 41 20 Analysis of experimental results: The MPP stable PCE of Example 1 is 22.78%, which is higher than that of Comparative Example 1 (19.02%) without a low-temperature curing functional layer; its HI is 0.026, which is significantly lower than that of Comparative Example 1 (0.105); and its trap state density is 2.7 × 10⁻⁶. 15 cm -3 This is lower than the 6.8 × 10⁻⁶ of Comparative Example 1. 15 cm -3 Its water contact angle is 101°, which is higher than that of Comparative Example 1 (61°); its 1000h PCE retention rate is 74%, which is higher than that of Comparative Example 1 (15%). This shows that by setting the low-temperature curing functional layer of the present invention between the perovskite light-absorbing layer and the second charge transport layer, it is possible to simultaneously improve interface defects, hysteresis, hydrophobic barrier and hygrothermal stability.
[0055] In Example 2, the MPP-stabilized PCE was 23.06%, the HI was 0.020, the PCE retention rate after bias holding was 94%, and the trap state density was 2.3 × 10⁻⁶. 15 cm -3 The PCE retention rate was 78% after 1000 hours. The initial photovoltaic performance and hysteresis of Example 2 were slightly better than those of Example 1, indicating that the ion-coordination-fluorosilicone dual-curing compound composed of perfluorooctylsiloxane segments, urea groups, imidazolium salt groups and epoxy groups can also achieve the core technical effects of the present invention.
[0056] Example 3 showed an MPP-stabilized PCE of 21.05%, an HI of 0.053, and a trap state density of 4.1 × 10⁻⁶. 15 cm -3 The water contact angle was 90°, and the PCE retention rate after 1000 hours was 52%. This result is weaker than that of Examples 1 and 2, but still better than Comparative Example 1. This indicates that when the content of functional compounds, initiator content, catalyst content, curing temperature, and functional layer thickness are at relatively low levels, the low-temperature cured functional layer can still play a certain role in interface regulation and stabilization.
[0057] Example 4 exhibited an MPP-stabilized PCE of 21.36%, an HI of 0.047, a water contact angle of 104°, and a PCE retention rate of 61% after 1000 hours. Example 4 had a higher water contact angle and better damp heat retention than most of the control groups in Comparative Examples 1 to 7, but its Jsc was 23.7 mA·cm. -2 This is lower than the 24.5 mA·cm in Example 1. -2 And 24.6 mA·cm in Example 2 -2 This indicates that a thicker or higher content of functional compounds in a low-temperature curing functional layer can enhance the barrier properties, but may have some impact on charge transport.
[0058] In Example 5, after adding nano-SiO2 with a fluorinated silane surface treatment, the water contact angle was 106° and the PCE retention rate after 1000 hours was 81%, both higher than those of Example 1 (101° and 74%). However, its MPP stable PCE was 22.32%, slightly lower than that of Example 2 (23.06%). These results indicate that surface-modified nano-barrier fillers are beneficial for improving hydrophobic barrier properties and hygrothermal stability, but their effect on initial photoelectric properties is not unidirectional. This aligns with the material principle that nanofillers may affect interfacial uniformity.
[0059] Comparative Example 2 used a common acrylate free radical photocurable layer, with a water contact angle of 88°, higher than the 61° of the blank Comparative Example 1, indicating that the common photocurable layer can provide a certain hydrophobic effect; however, its HI was 0.083, the PCE retention rate after bias voltage maintenance was 80%, and the PCE retention rate after 1000h was 34%, both significantly weaker than that of Example 1. These results demonstrate that the present invention does not rely solely on a common hydrophobic layer or a common free radical photocurable layer, but rather on the synergistic structure of an ion-coordination-fluorosilicone dual-curing compound and a cationic ring-opening curing system.
[0060] Comparative Example 3 uses a single siloxane self-crosslinking modified layer with a trap state density of 3.9 × 10⁻⁶. 15 cm -3 The water contact angle was 96°, indicating that the thiourea-based siloxane modification layer can provide certain defect passivation and hydrophobic effects; however, its HI was 0.070, and its PCE retention rate after 1000 hours was 41%, both weaker than those of 0.026 and 74% in Example 1. These results demonstrate that a single siloxane self-crosslinking modification layer is insufficient to replace the cationic halogen fixation structure and the cationic ring-opening curing structure in this invention.
[0061] Comparative Example 4 lacks a cationic halogen fixing group, and its trap state density is 3.2 × 10⁻⁶. 15 cm -3 The water contact angle is 100°, indicating that it still possesses certain interfacial defect regulation and hydrophobic effects due to the retention of thiourea and fluorosilicone segments; however, its HI is 0.092, the PCE retention rate after bias holding is 78%, and the PCE retention rate after 1000h is 30%, which is significantly weaker than that of Example 1. This result demonstrates that the cationic halogen fixed group makes an important contribution to reducing hysteresis, improving bias holding, and enhancing hydrothermal stability.
[0062] Comparative Example 5 lacks a Lewis base coordinating group, and its Voc is 1.112V, lower than 1.138V in Example 1; its trap state density is 4.9 × 10⁻⁶. 15 cm -3 This is higher than the 2.7 × 10⁻⁶ in Example 1. 15 cm -3This result demonstrates that Lewis base ligands contribute to reducing interfacial trap states and increasing open-circuit voltage. The water contact angle of Comparative Example 5 was 102°, close to that of Example 1, indicating that simply increasing hydrophobicity is insufficient to replace the regulatory role of Lewis base ligands on interfacial defects.
[0063] Comparative Example 6, lacking the fluorosilicone barrier segment, had a water contact angle of 74°, significantly lower than the 101° of Example 1; its 1000-hour PCE retention rate was 24%, significantly lower than the 74% of Example 1. These results demonstrate that the fluorosilicone barrier segment contributes to improving the hydrophobic barrier properties and hygrothermal stability of the functional layer. The trap state density of Comparative Example 6 was 3.1 × 10⁻⁶. 15 cm -3 This indicates that it can reduce interface defects to a certain extent because it still contains Lewis base coordination groups, but it is difficult to obtain sufficient hygrothermal stability after the absence of fluorosilicone segments.
[0064] Comparative Example 7 lacks epoxy groups or oxobutyl groups and does not contain a cationic ring-opening curable matrix. Its trapped state density is 3.0 × 10⁻⁶. 15 cm -3 The water contact angle is 95°, indicating that it still retains some interface passivation and hydrophobic effects; however, its MPP-stabilized PCE is 20.02%, the PCE retention rate after bias holding is 82%, and the PCE retention rate after 1000h is 20%, all of which are significantly weaker than that of Example 1. This result demonstrates that the low-temperature dual-curing network formed by epoxy groups and / or oxocyclic butyl groups and cationic ring-opening curable matrix plays an important role in stabilizing the interface functional layer and improving the long-term stability of the device.
[0065] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
[0066] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A low-temperature curing perovskite photovoltaic cell, comprising a transparent conductive substrate, a first charge transport layer, a perovskite light-absorbing layer, a second charge transport layer, and a back electrode, characterized in that, A low-temperature curing functional layer with a thickness of 5nm~120nm is disposed between the perovskite light-absorbing layer and the second charge transport layer. The low-temperature curing functional layer is formed by in-situ curing of the low-temperature curing composition. Based on a total mass of 100 parts of ion-coordination-fluorosilicone dual-curing compound, cationic ring-opening curable matrix, latent acid initiator and silane condensation catalyst, the low-temperature curing composition includes 15-70 parts of ion-coordination-fluorosilicone dual-curing compound, 25-85 parts of cationic ring-opening curable matrix, 0.1-4 parts of latent acid initiator and 0.01-1 parts of silane condensation catalyst. The ion-coordination-fluorosilicone dual-curing compound is a siloxane oligomer obtained by pre-hydrolysis condensation of fluorinated alkyl alkoxysilanes, Lewis base silanes, cationic silanes, and epoxy silanes and / or oxetane silanes; the siloxane oligomer simultaneously contains fluorosilicone barrier segments, Lewis base coordination groups, cationic halogen fixing groups, and epoxy and / or oxetane groups, and contains alkoxysilanes that can be further hydrolyzed and condensed.
2. The low-temperature curing perovskite photovoltaic cell according to claim 1, characterized in that, The molar ratio of the fluorinated alkyl alkoxysilane, Lewis base silane, cationic silane to epoxy silane and / or oxetane silane is 1~5:0.5~2:0.5~2:1~4.
3. The low-temperature curing perovskite photovoltaic cell according to claim 1, characterized in that, The fluorinated alkyl alkoxysilane is selected from one or two of trimethoxy(3,3,3-trifluoropropyl)silane and triethoxy(1H,1H,2H,2H-perfluorooctyl)silane; the Lewis base silane is selected from one or two of N,N'-bis(3-triethoxysilylpropyl)thiourea and 1-[3-(trimethoxysilyl)propyl]urea; the cationic silane is selected from one or two of N-[3-(trimethoxysilyl)propyl]-N,N,N-trimethylammonium chloride and 1-methyl-3-[3-(trimethoxysilyl)propyl]imidazolium chloride; the epoxy silane and / or oxetane silane is selected from one or two of 3-glycidoxypropyltrimethoxysilane and 3-ethyl-3-[[3-(triethoxysilyl)propoxy]methyl]oxetane.
4. The low-temperature curing perovskite photovoltaic cell according to claim 1, characterized in that, The thickness of the low-temperature curing functional layer is 8nm~80nm; the amount of the ion-coordination-fluorosilicone dual-curing compound is 20~55 parts.
5. The low-temperature curing perovskite photovoltaic cell according to claim 1, characterized in that, The cationic ring-opening curable matrix is selected from one or more of 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane, 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexane carboxylate, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and 3-ethyl-3-[[3-(triethoxysilyl)propoxy]methyl]oxetane.
6. The low-temperature curing perovskite photovoltaic cell according to claim 1, characterized in that, The low-temperature curing composition further includes surface-modified nano-barrier fillers; relative to the total mass of 100 parts of the ion-coordination-fluorosilicone dual-curing compound, the cationic ring-opening curable matrix, the latent acid initiator and the silane condensation catalyst, the surface-modified nano-barrier fillers are 0.1 to 5 parts.
7. The low-temperature curing perovskite photovoltaic cell according to claim 1, characterized in that, The perovskite light-absorbing layer is made of ABX3 type perovskite material, wherein the A-site cation includes one or more of methylamine ions, formamidinium ions, cesium ions, and rubidium ions; the B-site metal ion includes lead ions and / or tin ions; and the X-site halide ion includes one or more of iodide ions, bromide ions, and chloride ions. The first charge transport layer and the second charge transport layer are independently selected from electron transport layers or hole transport layers, respectively. The electron transport layer includes one or more of SnO2, TiO2, ZnO, C60, and PCBM, and the hole transport layer includes NiO. x One or more of PTAA, Spiro-OMeTAD, PEDOT:PSS, and CuSCN.
8. A method for preparing a low-temperature curing perovskite photovoltaic cell, characterized in that, Includes the following steps: S1. Provide a transparent conductive substrate and form a first charge transport layer on the transparent conductive substrate; S2. A perovskite light-absorbing layer is formed on the first charge transport layer; S3. Coat the side of the perovskite light-absorbing layer away from the first charge transport layer with a low-temperature curing composition; S4. The perovskite light-absorbing layer coated with the low-temperature curing composition is subjected to light irradiation treatment of 365 nm to 405 nm and heat treatment at 40°C to 100°C, so that the low-temperature curing composition forms a functional layer with a thickness of 5 nm to 120 nm in situ on the surface of the perovskite light-absorbing layer. S5. A second charge transport layer and a back electrode are formed on the low-temperature curing functional layer to obtain the low-temperature curing perovskite photovoltaic cell.
9. The method for preparing a low-temperature solidified perovskite photovoltaic cell according to claim 8, characterized in that, Before step S3, the method further includes the step of preparing the low-temperature curing composition: dissolving the cationic ring-opening curable matrix in a solvent, adding the ion-coordination-fluorosilicone dual-curing compound and stirring for 10 min to 120 min, then adding the latent acid initiator and the silane condensation catalyst, stirring in the dark for 5 min to 60 min, and then filtering through a 0.1 μm to 0.45 μm filter membrane; the solvent is selected from one or more of isopropanol, ethyl acetate, toluene, chlorobenzene, anisole, butyl acetate, methyl tert-butyl ether and fluoroether solvents.
10. The method for preparing a low-temperature solidified perovskite photovoltaic cell according to claim 8, characterized in that, In step S3, the coating method is spin coating, blade coating, slot coating, spray coating, or inkjet printing; when spin coating is used, the rotation speed is 1500rpm~5000rpm and the time is 10s~60s; in step S4, the 365nm~405nm light irradiation time is 10s~300s and the 40℃~100℃ heat treatment time is 1min~20min; after step S4, a post-processing step of standing at 20℃~60℃ for 30s~10min is also included.
